Αγροτικές προσφυγικές εγκαταστάσεις στη Μακεδονία: 1923-1930 - Κοντογιώργη Έλσα (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1992)
Over a million refugees entered the Greek state, following the Asia Minor Catastrophe (1922) and the compulsory exchange of populations between Greece and Turkey, creating tremendous problems of settlement. The principal object of the governments and the Refugee Settlement Commission (RSC) — an organisation supervised by the League of Nations — during the 1920s was the establishment of the refugees in rural settlements in the Northern part of Greece and particularly in the region of Macedonia. The aim of this paper is to examine the reasons that formulated this settling strategy. To this end I have drawn on material from archival and published sources in an attempt to provide, a systematic account of certain factors that affected the resettlement of refugees. The priority given to the resettlement of refugees in Macedonia in order to help them to become self-sufficient through agriculture depended on a complex interplay of a number of practical, economic, and political considerations: the demographic and topographic characteristics of the region in contrast with other parts of Greece; available Muslim properties and large estates, which could be expropriated; projects for the economic development of Macedonia with emphasis on the improvement of the agrarian sector; particular considerations of security and military requirements, especially in border areas coveted by neighbouring states; policies aimed at the national homogeneity of the population of Macedonia and the assimilation of slavophone Greeks. Finally, with reference to internal politics, the resettlement of the great bulk of refugees as smallholders in Macedonia was considered an effective way of eliminating the danger of social unrest and problems associated with a pauperised, landless, and therefore, radicalised peasantry as well as a means for the Venizelist camp to remain in power, given the pro-venizelist electoral behaviour of the refugees during this period.